Antioxidant, anti-tyrosinase and anti-quorum sensing activities of four mangrove tree species vs. green tea - Eric Wei Chiang Chan,Sin Mei Ng,Bexter Wee Kiong Sim,Huey Chee Tan,Zen Loong Lo (Journal of Applied Pharmaceutical Science, 2017)
This study was conducted to validate a claim that mangrove teas have stronger antioxidant and anti-tyrosinase properties than green tea. Different plant parts (leaves, stems and roots) of four mangrove tree species namely Rhizophora apiculata, Rhizophora stylosa, Avicennia rumphiana and Sonneratia alba were analysed their antioxidant, anti-tyrosinase and anti-quorum sensing (anti-QS) properties. Strongest antioxidant properties were observed in the stems of R. stylosa. Antioxidant properties of the mangrove species (fresh samples) and their teas (dried leaves) were inferior to leaves of Camellia sinensis and green tea, respectively. The anti-tyrosinase activity of leaves and stems of R. apiculata, and stems of S. alba was outstanding but was not detected in green tea. All four mangrove species possessed anti-QS properties with moderate activity displayed by green tea.
Keywords: Rhizophora apiculata,Rhizophora stylosa,Avicennia rumphiana,Sonneratia alba,Camellia sinensis.